Pendampingan Kesehatan Masyarakat melalui Pembuatan Apotek Hidup Desa Dunggala, Kec. Batudaa, Kab. Gorontalo - Muhammad Rezky Friesta Payu; Abdul Wahidin Nuayi (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
This KKN-Thematic Activity Program aims as an effort to improve health in the village of Dunggala especially during the Covid-19 pandemic to minimize / reduce and break the chain of spread of Covid-19. In the current pandemic, sufficient and good immunity is needed. Traditional medicine plays a role in maintaining the body's immunity. When compared to chemical drugs, folk remedies tend to be safer because the active substances in folk remedies are lower than those of chemical drugs. Therefore, the cultivation of medicinal plants is considered important. The method used in the KKN-Thematic program is the provision of examples of making live pharmacies and community development through socialization. This activity was held in Dunggala Village, Batudaa Subdistrict, Gorontalo Regency, and was integrated with Real Work Lecture (KKN), Research and Community Service Institute (LPPM) of Gorontalo State University (UNG) in 2021. This activity is supported directly by the Dunggala Village apparatus, led by the Dunggala Village Chief as a partner in this program.